ECONOMIC IMPACTS OF AN EARTHQUAKE DISASTER AND COVID-19 IN ALBANIA - Blerina BANUSHI; Iva SULAJ (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The earthquake, occurred on 26th November 2019, caused considerable material and financial damages. According to a document compiled by the Albanian Government with the support of several International Institutions, the earthquake affected directly and indirectly over 202,000 people, including 51 victims, 17,000 displaced and about 985 million Euros in damage, mainly to housing and educational infrastructure. Reconstruction under the same document will cost 1 billion 78 million Euros. As if that were not enough, the vast majority of the decline in economic activity during the post-earthquake period was “due to Covid-19 pandemic” of 2020. Therefore, the main aim of this study is to evaluate the long-term impacts of these two major events in the Albanian economy. The impacts of earthquake and pandemic damages are expected to have a resultant slowdown in the economic growth of Albania, caused mainly by unemployment, inflation and productivity decline in the main economic sectors. However, even if not stronger growth what will be needed in the future is the readiness to be reduced significantly unemployment and poverty. This will require progress on a number of priority reform areas, including ongoing reforms to Albania’s system of economic governance, which is more important than everything in this country. Loss compensation is the driving force of the post disaster recovery, and social productivity and sustainable economic development are the economic basis of compensation for disaster losses. To this end, economic development is the most effective way to compensate for disaster losses. At the end, the question that arises is: How will all this change the Albanian economy?